2008
DOI: 10.1542/peds.2008-1862
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Rickets and Vitamin D Deficiency in Infants, Children, and Adolescents

Abstract: Rickets in infants attributable to inadequate vitamin D intake and decreased exposure to sunlight continues to be reported in the United States. There are also concerns for vitamin D deficiency in older children and adolescents. Because there are limited natural dietary sources of vitamin D and adequate sunshine exposure for the cutaneous synthesis of vitamin D is not easily determined for a given individual and may increase the risk of skin cancer, the recommendations to ensure adequate vitamin D status have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
942
6
73

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,368 publications
(1,033 citation statements)
references
References 151 publications
12
942
6
73
Order By: Relevance
“…In accordance with current cut-off values (50-250 nmol/l) (Misra et al, 2008), 89% of the infants had sufficient 25(OH)D levels, which is a considerably higher prevalence than the level found in Danish teenage girls (Andersen et al, 2005). What defines an optimal concentration of 25(OH)D in children is an important question, but consensus has not been reached (Vieth, 2006;Wagner and Greer, 2008). Breastfeeding without vitamin D supplementation is a predictor of vitamin D deficiency (Gordon et al, 2008;Greer, 2008).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In accordance with current cut-off values (50-250 nmol/l) (Misra et al, 2008), 89% of the infants had sufficient 25(OH)D levels, which is a considerably higher prevalence than the level found in Danish teenage girls (Andersen et al, 2005). What defines an optimal concentration of 25(OH)D in children is an important question, but consensus has not been reached (Vieth, 2006;Wagner and Greer, 2008). Breastfeeding without vitamin D supplementation is a predictor of vitamin D deficiency (Gordon et al, 2008;Greer, 2008).…”
Section: Discussionmentioning
confidence: 81%
“…The Danish National Board of Health recommends that term infants should be given a vitamin D supplement (10 mg/day) for the first 24 months of life. At present, there is no agreement as regards the definition of what might be an optimal vitamin D status for infants and children (Wagner and Greer, 2008). There is no updated information on the vitamin D status of healthy Danish infants.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CAS in children is not clear. Vitamin D supplementation to prevent vitamin-D-deficient rickets in children is generally recommended [180], but there are some reports of children with hypercalcemia after treatment with vitamin D [181]. The classic symptoms consist of hypercalcemia, various degrees of renal failure, and metabolic alkalosis [182].…”
Section: Alkali Administration (Non-chloride-depletion Metabolic Alkamentioning
confidence: 99%
“…Because low serum 25-OH-D and osteomalacia has been reported in patients with NF1 and low bone mass, patients should be evaluated for vitamin supplementation. The recent change in reference standards for serum 25-OH-D from 10 ng/ml, considered the ''rachitic'' value for many years, to 20 ng/ml (50 nmol/L) [Wagner and Greer, 2008;Mimouni and Shamir, 2009], has implications on the need for intervention and effective dosing. A study using 1,000 IU vitamin D to correct serum levels in four patients with NF1 reported increased BMD [Seitz et al, 2009], while a lower dose of 400 IU in another study did not improve BMD [Bruenetti-Pierri et al, 2008].…”
Section: Osteoporosismentioning
confidence: 99%